NEXUS Gains Talk 11: Integrating Water Resources Management in a Shared River Basin - Velpuri, Naga Manohar; Etichia, Mikiyas; Lautze, Jonathan F. (CGIAR System Organization, 2023)
This webinar discusses application of a nexus tool to support water allocation reform in the Incomati Basin. NEXUS Gains has partnered with INMACOM and the University of Manchester to build a robust and comprehensive river basin systems model using an open-source Python water resources (Pywr) framework that accounts for water demands from agriculture, domestic, industry, and energy sectors. This webinar outlines the process of model co-development and presents preliminary results centering on emerging opportunities to foster greater benefits through more collective basin management.